Quantifying monochromatic and polychromatic optical blur anisotropy in the periphery of myopes and emmetropes using a radial asymmetry metric - Degre Kendrick, Chloe; Pusti, Dibyendu; Yoon, Geunyoung (Frontiers in Medicine, 2025)
PurposeThe goal of this study is to characterize peripheral blur anisotropy resulting from monochromatic and chromatic aberrations along multiple meridians of myopic and emmetropic eyes using a newly developed quantitative metric.MethodsA scanning Shack-Hartmann-based wavefront sensor was used to measure lower- and higher-order monochromatic aberrations along the horizontal and vertical meridians of 20 healthy adult subjects (10 myopes, and 10 emmetropes). Monochromatic and polychromatic blur asymmetry magnitude and orientation were quantified using a novel metric based on the optical transfer function. Published population averages of longitudinal and transverse chromatic aberration were used for polychromatic blur asymmetry calculations.ResultsBlur anisotropy magnitude and orientation differed between refractive groups at several peripheral retinal locations under monochromatic and polychromatic conditions. Myopes were significantly more likely to have vertically oriented blur than emmetropes under monochromatic conditions in the temporal peripheral retina beyond 20°. These differences were minimized when chromatic aberrations were included, though the trend remained the same.ImplicationsA trend of more vertical optical blur in the temporal periphery of myopes strengthens the hypothesis that myopes experience different peripheral optical blur than emmetropes, though the small sample size of the current study limits generalizability of the results. A thorough account of peripheral blur across the visual field may lead to a better understanding of the cues that the peripheral visual system might rely on during processes such as accommodation, emmetropization, and myopization.